Molecular Characterization Of Blandm And Blaoxa-48 Gene In Carbapenam Resistant Klebsiella Species At A Tertiary Care Centre - Mishra, Aditya; Khandait, Manisha; Sandhya, Sandhya; Agwan, Vivek (Journal of Neonatal Surgery, 2025)
Introduction: Carbapenems are the last resort drugs used to treat multidrug resistant (MDR) bacterial infections. The incidence of carbapenem resistance is increasing across the globe. Treatment failure and eventually high mortality were reported among individuals with carbapenem resistant bacterial infections. The incidence of carbapenem-resistant Klebsiella pneumoniae (CRKP) infections is increasing globally. The blaNDM is the predominant carbapenem-resistant gene in CRKP isolates. However, blaOXA-48 has also been reported to be increasing in recent days. Aim And Objective: To study the molecular characterization of blaNDM and blaOXA-48 gene in carbapenam resistant klebsiella isolates. Material And Methods: This was a Cross sectional study carried out in the Department of Microbiology for a period of 18 months i.e, November 2022 to May 2023. A total of 300 Klebsiella species from the isolates were tested collected from hospitalized and consultation patients were included in the study. The Antimicrobial susceptibility testing was performed according to the CLSI guidelines . The DNA extraction was done using the Qiagen DNA extraction kit and the resistant gene blaNDM and blaOXA-48 was detected using the PCR. Results: A total of 300 Klebsiella species from the isolates were tested out of which Carbapenamses resistant kKbspp was observed to be 204(68%) and Carbapenamses sensitive Kbspp with 96 (32%) with the prevalence rate of 68%. The ratio of females was observed to be more as compared to the males with 64% and 36% respectively with the age group of 30-40 (38.7%) been affected the most. The maximum isolates were from urine (55%) and least for body fluid with 3%. The Ratio of Male/Female amongst Carbapenamses resistant klebsiella isolates was observed to be 32.9% and 67.1 % respectively. The age group 30-40 was the most commonly affected in Carbapenamses resistant klebsiella isolates with the urine cases most commonly found with 51.4%. The molecular characterization confirms BLANDM gene 48 (23.5%) and BLAOXA-48 with 57 (27.9%) was expressed. Conclusion: CRKP is emerging as a serious threat among drug-resistant bacterial pathogens which would complicate the treatment of bacterial infections with available antibiotics. Performing regular surveillance studies in hospitals is very important to identify the circulating genes among carbapenem-resistant bacteria which will help to overcome the therapeutic challenges in treating the patients infected with CRKP